The patient journey project in Italian mental health services: results from a co-designed survey on clinical interventions and current barriers to improve the care of people living with schizophrenia - Vita, Antonio; Barlati, Stefano; Porcellana, Matteo; Sala, Elisa; Lisoni, Jacopo; Brogonzoli, Luisa; Percudani, Mauro Emilio; Iardino, Rosaria (Frontiers in Psychiatry, 2024)
Introduction The Patient Journey Project aimed to analyze the scenario among Italian Mental Health Services (MHS) to understand the clinical interventions that are properly implemented and the ones deserving further implementation to design an effective treatment plan for patients living with schizophrenia (PLWS). Methods The 60-items survey was co-designed with all the stakeholders (clinicians, expert patients and caregivers) involved in the Patient Journey and focused on three phases of schizophrenia course: early detection and management, acute phase management, long-term management/continuity of care. Respondents were Heads of the Mental Health Departments and Addiction Services (MHDAS) or facilities directors throughout Italian MHS. For each statement, respondents expressed the consensus on the importance and the degree of implementation in clinical practice. Results Considering the importance of the statement, strong consensus was reached for most of the statements. Good levels of implementation were found on 2/17 statements of early detection and management, on 3/16 statements for acute phase management and on 1/27 statements of long-term management/continuity of care. Poor levels of implementation were found on 1/17 statements of early detection and management, none of acute phase management, and 4/27 statements for long-term management/continuity of care. Moderate levels of implementation were found on 14/17 statements for early detection and management, on 13/16 statements of acute phase management, and on 22/27 statements of long-term management/continuity of care. Thus, among Italian MHDAS, most interventions for PLWS were moderately implemented in clinical practice. Discussion Italian MHS have to provide new strategies and structural actions to overcome these current limitations and barriers to effectively improve the journey of PLWS. The areas that deserve most implementation include interventions during the early stage (especially the continuity of care between Child and Adolescent Mental Health Services and Adult Mental Health Services), the evidence-based psychosocial interventions during the chronic stages of the disorder, and the continuity of care after acute hospitalization.